2000
DOI: 10.1002/1097-0339(200012)23:6<422::aid-dc13>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated histoplasmosis with reactive hemophagocytosis: Aspiration cytology findings in two cases

Abstract: Two cases of disseminated histoplasmosis associated with reactive hemophagocytic syndrome are described. The clinical presentation was with prolonged unexplained fever and hepatosplenomegaly. On a strong clinical possibility of tuberculosis, antitubercular treatment was initiated in both patients. Lymph node (case 1), splenic (case 2), and bone marrow aspiration, however, showed sheets of proliferating histiocytes, and intracellular and extracellular histoplasma organisms. Aspiration cytology was thus valuable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Disseminated tuberculosis and histoplasmosis may cause hemophagocytosis with fever of unknown origin [21,22]. In our series, four patients with FUO also had hemophagocytotic syndrome.…”
Section: Discussionmentioning
confidence: 50%
“…Disseminated tuberculosis and histoplasmosis may cause hemophagocytosis with fever of unknown origin [21,22]. In our series, four patients with FUO also had hemophagocytotic syndrome.…”
Section: Discussionmentioning
confidence: 50%
“…Subramanian et al (9) report 18 additional cases diagnosed in India. Review of the literature revealed 51 more cases in India, 3 probable cases, 1 unpublished case mentioned in a review, and 2 cases from personal communications (13–48). Thirteen cases have been diagnosed in the United Kingdom in patients with prior residence on the Indian subcontinent (10), and 1 case was diagnosed in Canada in a patient who had recently traveled to India (49).…”
Section: Discussionmentioning
confidence: 99%
“…1 It is also observed in hairy cell leukemia, Hodgkin's disease, certain types of acute leukemia, and certain high-grade epithelial malignancies. 2 Reactive hemophagocytosis associated with disseminated histoplasmosis has been reported in the aspiration cytology of spleen and lymph nodes by Kumar et al 3 Association of reactive hemophagocytosis with tuberculosis has not been reported to our knowledge.…”
Section: Discussionmentioning
confidence: 92%